Ferroptosis as the new approach to cancer therapy - Ojo, Oluwafemi Adeleke; Grant, Susan; Nwafor-Ezeh, Pearl Ifunanya; Maduakolam-Aniobi, Tobiloba Christiana; Akinborode, Tolulope Isaiah; Ezenabor, Emmanuel Henry; Ojo, Adebola Busola (ELSEVIER, 2025)
Cancer is characterized by unregulated cell proliferation, evasion of apoptosis, and a propensity for metastasis, making it a leading cause of morbidity and mortality globally. Major challenges in cancer treatment include drug resistance and tumor heterogeneity, which hinder the clinical efficacy of existing therapies. To enhance treatment outcomes, it is essential to integrate emerging biological insights and technological advancements with conventional therapeutic strategies. Recent research has identified various forms of cell death, which can be classified as either regulated or unregulated. Regulated cell death involves specific biochemical and signaling pathways, while unregulated cell death occurs passively and uncontrollably. Apoptosis, the most extensively studied form of regulated cell death, is primarily mediated by the activation of caspase proteases. Nevertheless, the resistance of many tumors to apoptotic pathways has shifted focus towards non-apoptotic forms of cell death, such as ferroptosis. Ferroptosis is an iron-dependent form of regulated necrosis characterized by extensive membrane damage resulting from lipid peroxidation. Numerous preclinical studies have demonstrated that inducing ferroptosis can significantly reduce tumor growth across a variety of cancer types. For instance, in a study involving breast cancer models, the use of ferroptosis inducers such as erastin and RSL3 led to a marked decrease in tumor volume and weight.
This review aims to explore the potential of ferroptosis as a novel therapeutic strategy in cancer treatment.